NUTRITION FOR TEENS OF STATE AGRESTE ALAGOAS (Fiep Bulletin - online, 2016)
The monitoring of nutritional status is an important living conditions of children and adolescents, besides allowing that check the health status over certain periods of a given population. This study aimed to evaluate the nutritional status of schoolchildren enrolled in public schools teaching the Alagoas harsh. The sample consisted of 610 students of both sexes, the age group 9-14 years, with 302 male and 308 female, chosen randomly among students duly enrolled in four schools in the municipal Star of Teaching Alagoas - AL, in 2012. For data collection was used: one Sanny® stadiometer and balance Techline BAL-150PA®. Children and adolescents were classified as normal weight, overweight (EP) and obesity (OB) according to BMI / age, according to the limits proposed by Conde and Monteiro. For the treatment of the data to central tendency and dispersion statistical values ??was used. It can be concluded that as many boys as girls, mostly showed normal BMI for age. However, it is noteworthy that found high overweight and obesity prevalence in school the wild Alagoas region.
Keywords: Nutritional status; BMI; School.